Hilar lymphocele following blunt trauma - (:unkn) unknown (SPRINGER, 1999)
We present a case of traumatic hilar lymphocele which occurred following blunt trauma without any reported injury.
Keywords: traumatic lymphocele; MR; CT-guided aspiration; X-ray; hilum; THORACIC-DUCT CYST